Application and microbial ecology of psychrotrophs in domestic wastewater treatment at low temperature. (January 2018) - Xu, Zhenzhen; Ben, Yue; Chen, Zhonglin; Jiang, Anxi; Shen, Jimin; Han, Xiaoyun
Abstract: The feasibility of a bunch of screened psychrotrophs being applied to low-temperature wastewater treatment was investigated. The screened psychrophillic strains are capable of growth at a broad temperature-range from 0 to 40 °C and exhibit a preferable TTC-dehydrogenase activity at low temperature (4–10 °C). Along the sharply fluctuant temperatures (25–4–25 °C), the screened psychrotrophs (compared with the indigenous mesophiles) demonstrate less fluctuations of COD removal and more rapid recovery after temperature shocks. COD removal of approximate 80% was recorded by single psychrotrophs (while only 10% by single mesophiles) at low temperature (4 °C). Soft polyurethane foam showed better performance for psychrotrophs immobilization, with the optimal filling rate of 30% (v/v) in the bioreactor. The observation shows that the immobilized psychrotrophs demonstrated a relatively high performance on both conventional and emerging organic contaminants removals at low temperature. In order to check the feasibility of the screened psychrotrophs in treating actual domestic wastewater, a pilot-scale ICABR bioreactor was operated firstly at low temperature (4 °C) and then at seasonal varying temperatures (0–30 °C) for one year, the influent COD of 150–600 mg L −1 was efficiently reduced to 40 ± 18 mg L −1 under the conditions of an overall hydraulic retention time of 10 h. Furthermore, psychrotrophs performed stably as the predominant bacteria family during the whole operation. This study provides evidence that microbial intensification with psychrotrophs was a feasible strategy to improve the efficiency of conventional wastewater treatment process at low temperature. Graphical abstract: Image 1 Highlights: Identified as Pseudomonas, Bacillus, Sphingobacterium, Shewanella, Serratia, Arthrobacter. Broad growth-range from 0 to 40 °C and powerful TTC-dehydrogenase activity at low temperature. Immobilization on soft polyurethane foam led to better performance and stable microbe population. Efficient and stable degradation of COD and p CNB in actual domestic wastewater at 4 °C. Predominant and changeless family in a pilot-scale ICABR bioreactor at seasonal temperatures.